2018
DOI: 10.1021/acs.jafc.7b05719
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the Molecular-Mechanisms and In Vivo Evaluation of the Anti-inflammatory Effect of Alginate-Derived Seleno-polymannuronate

Abstract: Alginate-derived polymannuronate (PM) is a type of polysaccharide found in edible brown seaweeds. Seleno-polymannuronate (Se-PM) was prepared from PM via synthesis using sulfation- and selenation-replacement reactions. The anti-inflammatory activity of Se-PM and its corresponding molecular mechanisms were investigated. In lipopolysaccharide (LPS)-activated murine macrophage RAW264.7 cells, Se-PM significantly attenuated the production of nitric oxide (NO), prostaglandin E (PGE), and reactive oxygen species (RO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 45 publications
3
21
0
Order By: Relevance
“…Of note, the primary role of ROS during inflammation has also been found (Bi et al., ). The overproduction of ROS not only leads to oxidative stress but also exacerbates the inflammation (Nam, Son, Yang, Lee, & Lee, ).…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…Of note, the primary role of ROS during inflammation has also been found (Bi et al., ). The overproduction of ROS not only leads to oxidative stress but also exacerbates the inflammation (Nam, Son, Yang, Lee, & Lee, ).…”
Section: Introductionmentioning
confidence: 81%
“…Indeed, we also found the products of NO and PGE2 increased with the overexpression of iNOS and COX‐2. Previous study has reported that NO and PGE2 are critical inflammatory mediators and release during the inflammatory response (Bi et al., ). Therefore, it's crucial to suppress the products of iNOS and COX‐2.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations